Activity Patterns and Thermoregulatory Behavior of the Viviparous Lizard Phymaturus palluma in Aconcagua Provincial Park, Argentine Andes - Vicenzi, Nadia Pamela (2019)
Temperature has a significant influence on physiology, ecology, and life history of ectotherms. Despite environmental fluctuations, lizards have developed behavioral mechanisms to maintain a relatively constant body temperature. These behaviors are particularly important for lizards living at high elevations like the high mountain lizard Phymaturus palluma, an endemic lizard to Central Andes. We studied how this species thermoregulates throughout the day and how abiotic and biophysical factors influence their activity. We recorded lizard activity and body postures and orientations at different times of the day during two seasons. Results indicate that P. palluma invest most of their time and energy in thermoregulation to maintain an optimal body temperature. Lizards activity raised with operative temperature of sun-exposed rocks up to an optimum and declined above that temperature. In addition, activity was negatively correlated with crevice temperature and positively correlated with mean operative temperature. Lizards changed their heat source along the day, using heliothermy most part of daytime and thigmothermy in the afternoon. Body postures were related to operative temperatures, so they may play an important role in thermoregulation. In contrast, body orientations were not related to operative temperatures. This study supports the idea that the benefit of thermoregulatory behaviors exceeds the energetic costs and the risk of predation involved in basking activities.